Kemampuan Profesional Mahasiswa Praktik Lapangan Kependidikan (Studi Mahasiswa Departemen Sosiologi Tahun Ajaran 2021/2022) - Abkoria, Tia; Nora, Desri (Universitas Negeri Padang, 2022)
The purpose of this study is to analyze the professional abilities of students in the field of education in the sociology department for the 2021/2022 academic year. The method used in this research is qualitative with case study research type. The informant selection technique is purposive sampling with a total of 10 informants. The theory used in this research is the Structural Functional theory by Talcott Parsons. This study uses data analysis from the Miles and Huberman model. Based on the results of this study, students of the Department of Sociology have been able to carry out basic teaching skills in professional competence as a teacher as follows: (1) Ability to understand educational foundations, (2) Understanding in the field of educational psychology, (3) Have been able to implement the learning process from beginning to end, (4) the ability to develop learning programs, (5) the ability to carry out learning evaluations, (6) the ability to carry out variations in learning, (7) the ability to design and utilize various media and learning resources, (8 ) The ability to master the subject matter in accordance with the field of study being taught, (9) The ability to manage the class.